Post traumatic near total amputation of apex of tongue: a rare case report - Gupta, Madhusoodan; Varshney, Deepti (International Surgery Journal, 2021)
Post traumatic near total amputation of apex of tongue is a rare scenario but when happens it causes life threatening situation due to active intraoral bleeding and risk of aspiration especially in children. Tongue is a unique organ which has very rich blood supply and resides in intraoral cavity. Due to its rich blood supply profuse bleeding is commonly seen after the tongue injury. It helps in swallowing, speech, taste, mastication and airway protection. It facilitates perception of gustatory stimuli. Here author presents a case of 13 months old female child, who presented to emergency department with history of fell down from the bed and sustained tongue injury with profuse bleeding. On examination patient had near total amputation of apex of tongue. Gentle debridement followed by meticulous complex repair of intrinsic muscles of tongue was done. On post-operative day two patient was discharged uneventfully.